Double-Cut Tibial Plateau Leveling Osteotomy for the Management of Cranial Cruciate Ligament Insufficiency in Dogs with an Excessive Plateau Angle: Early Clinical Results in 16 Dogs - Curuci, Eloy H. P.; Minto, Bruno W. [UNESP]; Magalhães, Thais V. [UNESP]; De Barros, Luciano P. [UNESP]; Dias, Luis Gustavo G. G. [UNESP] (Thieme, 2024)
Objective To describe a modification of the tibial plateau leveling osteotomy technique wherein a double cut is made in the same plane to level the tibial plateau (double-cut tibial plateau leveling osteotomy [DCTPLO]) for treating dogs with cranial cruciate ligament (CrCL) and excessive tibial plateau angle (eTPA) diseases. Study Design The DCTPLO technique was performed on 18 stifles in dogs with CrCL and an eTPA (>34°). This study evaluated the accuracy of preoperative planning, feasibility of the technique, postoperative clinical outcomes, radiographic examinations at the postoperative follow-up for the first 120 days, evolution of the tibial plateau angle (TPA), time of union of the osteotomy, apposition of the implants, and possible complications. Results The described technique proved to be feasible for clinical application, with reproducibility from preoperative planning. An effective reduction in the eTPA levels was observed. The mean preoperative and postoperative TPA values were 39.4° (36°-43.5°) and 6.3° (3°-13°), respectively. Radiographic healing time was 60 days in 17/18 of stifles. Minor complications (not requiring surgical review or clinical treatment) were observed in 4/18 of stifles. Conclusion The DCTPLO technique was effective for treating CrCL disease with TPA of up to 43.5° in dogs.
Keywords: cranial cruciate ligament; double cut; osteotomy; tibial plateau leveling osteotomy; TPLO